The Influence of Employee Characteristics and Behavior on Employee Morale: Study at one of the Cimahi City Government Agency Offices - Adinata, Ujang Wan Sam (LPPM STMIK Mardira Indonesia, 2023)
This study is driven by decreased employee productivity influenced by inadequate work motivation, possibly caused by a discrepancy between employee expectations and the actual working conditions. Factors thought to influence work excitement include individual traits and employee practices. This study aims to thoroughly examine the direct and indirect effects of individual traits and behaviors on employee work excitement in the Investment and Integrated One-Stop Service Office (DPMPTSP) of Cimahi City. This study employs route analysis to examine a population study of 56 employees in the DPMPTSP of Cimahi City. The research findings suggest that individual traits (X1) account for 50.00% of the influence. Individual behavior directly influences 32.70% of the whole outcome. The R-squared value indicates that the combined influence of individual attributes, individual behavior, and job excitement accounts for 82.70% of the variability in work enthusiasm. These findings emphasize the significance of comprehending and controlling employees' unique traits and actions to improve their motivation at work and, ultimately, the organization's success.